Muscle : the gripping story of strength and movement - Meals, Roy A. (W.W. Norton & Company, 2023)
"Muscle tissue powers every heartbeat, blink, jog, jump, and goose bump. It is the force behind the most critical bodily functions, including digestion and childbirth, as well as extreme feats of athleticism. While most of our organs remain invisible to us, we can mold our muscles with exercise and observe the results. In this eye-opening book, orthopedic surgeon Roy A. Meals takes us on a wide-ranging journey through anatomy, biology, history, and health to unlock the mysteries of our muscles. He illustrates the molecular processes at work when our muscles contract and breaks down the three different types of muscle -- smooth, skeletal, and cardiac -- to reveal their unique and often reflexive functions in our bodies. As informative as it is engaging, Muscle explains the major advancements in medicine, from the development of the EKG machine to muscle transplants and cutting-edge gene-editing research. Meals describes the causes and treatments for common ailments like cramps and strains, as well as rare genetic disorders like muscular dystrophy. He investigates the science behind popular fitness trends, including how resistance training builds our muscles, what it means to "feel the burn," and the varied benefits of stretching, warming up, or cooling down. Along the way, Meals offers insight into the chaning aesthetic and cultural conception of muscle, from Michelangelo's David to present-day bodybuilders, and detours into the animal kingdom to discover specialized muscles that control a bird's song or a whale's blowhole. Brimming with fun facts, lucid illustrations, and infectious enthusiasm, Muscle sheds light on the astonishing, essential tissue that moves us through life"--Pages 2 -3 of cover